2006
DOI: 10.1007/s10499-006-9059-9
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of growth, survival rate and number of marketable koi carp produced under different management regimes in earthen ponds and concrete tanks

Abstract: To compare the growth performance of koi carp, Cyprinus carpio var. koi, produced in concrete tanks (2.13 · 0.91 · 1.22 m; capacity: 2,000 l each) and earthen ponds (9.1 · 6.10 · 1.07 m; capacity: 59650 l each), fish larvae (stocking size: 0.12 ± 0.008 g) were cultured for 11 weeks and individual weight gain, survival rate and number of marketable fish produced were compared among four management regimes for each culture system: (1) live zooplankton fed to fish larvae in ponds (PLF) and tanks (TLF); (2) applic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 12 publications
0
17
1
Order By: Relevance
“…1) could be related to the acidic nature of water bodies in North Bengal (Nath et al, 1994;. Lower range of pH values in the PM and CD ponds could be attributed to the animal manure applied in these treatments (Jha et al, 2004;Jha et al, 2006;Jha et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1) could be related to the acidic nature of water bodies in North Bengal (Nath et al, 1994;. Lower range of pH values in the PM and CD ponds could be attributed to the animal manure applied in these treatments (Jha et al, 2004;Jha et al, 2006;Jha et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Since ornamental fish ponds in India are much smaller compared to other aquaculture ponds (measuring about 7 m×20 m, with an average depth of 0.6-1.0 m), there are more opportunities to control environmental conditions in ornamental fish ponds by employing proper management techniques. Introduction of live zooplankton has been investigated as a practicable alternate to pond fertilization for increasing ornamental fish yields while avoiding water quality deterioration (Jha & Barat, 2005a;Jha et al, 2006;Jha et al, 2007). However, there is a paucity of documentation pertaining to bacteriological parameters of ornamental fish ponds, particularly those under live-food and manure based management regimes.…”
mentioning
confidence: 99%
“…Studies on feeding behaviour and food selection of koi carp and goldfish indicated a strong preference for cladocerans and negative selection of copepods and phytoplankton (Jha and Barat, 2005b;Jha et al, 2006b). Significantly higher growth and survival rates were observed in koi carp fry fed with exogenous plankton, compared with pelleted diet (Jha and Barat, 2005b;Jha et al, 2006a;Jha et al, 2007). In the only report available to the author on the husbandry of rainbow shark, a combination of greenwater infusoria (including mainly ciliates) with artificial diets yielded better growth, compared to fish fed with artificial feed only (McGovern-Hopkins et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Among literatures available, the values range from less then 0.3 fish/l for the guppy, Poecilia reticulata cultured in outdoor tanks and fed with different types of live and formulated diets (Fernando and Phang, 1985) and 0.4 fish/l in angelfish, Pterophyllum scalare cultured in indoor tanks and fed with a commercial trout diet containing 45% protein (Degani, 1993) to 0.5 fish/l for the gourami, Trichogaster trichopterus stocked in outdoor tanks and fed with formulated diet (Cole et al, 1997). The koi carp, Cyprinus carpio are cultured at a density of 0.25 fish/l in Hawaii (reported in Asano et al, 2003) and 0.3 fish/l in India in outdoor tanks and ponds fed with either pelleted diet or live plankton (Jha and Barat, 2005a;Jha and Barat, 2005b;Jha et al, 2006a;Jha et al, 2007). The goldfish, Carassius auratus has also been cultured at a density of 0.3 fish/l in outdoor ponds and fed with live plankton (Jha et al, 2006b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation